MicroRNAs in renal fibrosis - Chung, Arthur C.; Lan, Hui Y (Frontiers in Physiology, 2015)
MicroRNAs (miRNAs) are endogenous short noncoding RNAs that regulate most of important cellular processes by inhibiting gene expression through the post-transcriptional repression of their target mRNAs. . In kidneys, miRNAs have been associated in renal development, homeostasis, and physiological functions. Results from clinical and experimental animal studies demonstrate that miRNAs play essential roles in the pathogenesis of various renal diseases. Chronic kidney diseases (CKD) is characterized by renal fibrosis. Transforming growth factor beta (TGF-β) is recognized as a major mediator of renal fibrosis because it is able to stimulate the accumulation of extracellular matrix proteins to impair normal kidney function. Recently, emerging evidence demonstrate the relationship between TGF-β signaling and miRNAs expression during renal diseases. TGF-β regulates expression of several microRNAs, such as miR-21, miR-192, miR-200, miR-433, and miR-29. MiR-21, miR-192, and miR-433 which are positively induced by TGF-β signaling play a pathological role in kidney diseases. In contrast, members in both miR-29 and miR-200 families which are inhibited by TGF-β signaling protect kidneys from renal fibrosis by suppressing the deposition of extracellular matrix and preventing epithelial-to-mesenchymal transition, respectively. Clinically, the presence of miRNAs in blood and urine has been examined to be early biomarkers for detecting renal diseases. From experimental animal studies of CKD, targeting microRNAs also provides evidence about therapeutic potential of miRNAs during renal diseases. Now, it comes to the stage to examine the exact mechanisms of miRNAs during the initiation and progression of renal diseases. Therefore, determining the function of miRNAs in renal fibrosis may facilitate the development of both early diagnosis and treatment of renal diseases.